2021
DOI: 10.3390/biom11121845
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin-3-Gallate Diminishes Intra-and Extracellular Amyloid-Induced Cytotoxic Effects on Cholinergic-like Neurons from Familial Alzheimer’s Disease PSEN1 E280A

Abstract: Alzheimer’s disease (AD) is a complex neurodegenerative disease characterized by functional disruption, death of cholinergic neurons (ChNs) because of intracellular and extracellular Aβ aggregates, and hyperphosphorylation of protein TAU (p-TAU). To date, there are no efficient therapies against AD. Therefore, new therapies for its treatment are in need. The goal of this investigation was to evaluate the effect of the polyphenol epigallocatechin-3-gallate (EGCG) on cholinergic-like neurons (ChLNs) bearing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…EGCG has received significant attention because of its protective role in health and disease . In particular, EGCG impedes aggregation of tau, disassembles preformed tau filaments, , reduces tau hyperphosphorylation or glycation, and suppresses tau expression . Our study, by systematically investigating the regulatory effect of EGCG on tau LLPS, provides novel insights into the biological activity of EGCG.…”
Section: Discussionmentioning
confidence: 91%
“…EGCG has received significant attention because of its protective role in health and disease . In particular, EGCG impedes aggregation of tau, disassembles preformed tau filaments, , reduces tau hyperphosphorylation or glycation, and suppresses tau expression . Our study, by systematically investigating the regulatory effect of EGCG on tau LLPS, provides novel insights into the biological activity of EGCG.…”
Section: Discussionmentioning
confidence: 91%
“…It is known that ROS/ H 2 O 2 activate c-JUN, P53, pro-apoptotic PUMA, and CASPASE-3 48 . Unsurprisingly, immunocytochemistry analysis showed that WT ChLNs display neither activated c-JUN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, EGCG significantly inhibits the aggregation of the protein sAPPβ and reverses Ca 2+ -induced neuroinflammatory responses. It also modulates Ca 2+ endocytosis, inhibits the activation of the transcription factor NF-kappa B, and reduces the secretion of pro-inflammatory IL-6 in astrocyte-like cells, thus inhibiting inflammation and exerting neuroprotective effects [ 45 ]. However, despite numerous studies investigating the specific mechanisms of EGCG's neuroprotective effects on AD molecular, its pharmacological mechanisms remain largely unexplored, and strategies for its use in AD treatment require further exploration [ 46 ].…”
Section: Discussionmentioning
confidence: 99%